The IGAD Climate Adaptation Strategy (2023-2030): Summary - Intergovernmental Authority on Development Centre of Excellence for Climate Adaptation and Environmental Protection (IGAD CAEP) (2023)
This document summarises the IGAD Climate Adaptation Strategy (2023-2030). The IGAD Climate Adaptation Strategy provides a framework for collaborative efforts to mitigate climate risks and bolster the resilience and adaptive capacities of IGAD Member States. Embracing a comprehensive societal approach to resilience, the Strategy outlines realistic and attainable near-, medium-, and long-term targets. As the first-ever regional-wide adaptation Strategy, it underscores IGAD's renewed dedication to climate adaptation as a central development priority. Beyond that, it offers a unique opportunity to shape a future for the IGAD region that is not only climate-resilient but also characterized by peace and prosperity.